Readiness of Canggu Village Bali as digital nomad tourism - Putu Herny Susanti (Universitas Merdeka Malang, 2023)
The health crisis due to the Covid-19 virus has an impact on decreasing tourist visits, resulting in a decline in tourism sector income. Tourism trends have changed in light of the prohibition ban. One alternative tourism that can follow current trends is digital nomadic tourism. The tour is intended to attract digital nomads to work while traveling. Based on this review, this study aims to analyze the readiness of Canggu Village in Bali as digital nomad tourism. This study is a qualitative descriptive research model that uses data collection techniques consisting of a literature review. The findings conclude that the readiness of Canggu Village as digital nomadic tourism is from the components of attractions and facilities that can support the needs of digital nomad tourists. Meanwhile, in the additional service and accessibility components, there are still shortcomings such as the absence of sidewalk facilities and safe crossings for pedestrians, narrow road conditions and heavy traffic.